2004
DOI: 10.3200/aeoh.59.8.410-417
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and Psychological Characteristics of Noise-Sensitive Adults in Finland

Abstract: The authors examined the relationship of noise sensitivity with health status and psychological factors in individuals <70 yr of age in Finland. Subjects (n = 1,355) were selected from a 1988 case-control study, based on the Finnish Twin Cohort, that assessed noise sensitivity, lifetime noise exposure, and hypertension. Other health status and psychological factors were obtained from a questionnaire that had been administered to the same individuals in 1981. Statistical analysis showed that noise sensitivity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Zimmer and Ellermeier [66] reported only a tendency in the same direction when measuring NS with the LEF, probably due to the limited age range in this study. On the other hand, Heinonen-Guzejev et al, [67] observed a decrease of NS (measured with the WNS) with age, whereas Stansfeld et al, [31] found the highest NS (using a single-item self-report and the McKennell scale for sensitivity measurement) among middle-aged women (30-44 years) and a declining sensitivity in older age groups.…”
Section: Noise Sensitivity and Agementioning
confidence: 96%
“…Zimmer and Ellermeier [66] reported only a tendency in the same direction when measuring NS with the LEF, probably due to the limited age range in this study. On the other hand, Heinonen-Guzejev et al, [67] observed a decrease of NS (measured with the WNS) with age, whereas Stansfeld et al, [31] found the highest NS (using a single-item self-report and the McKennell scale for sensitivity measurement) among middle-aged women (30-44 years) and a declining sensitivity in older age groups.…”
Section: Noise Sensitivity and Agementioning
confidence: 96%
“…Noise sensitivity has been associated with neuroticism [2] and smoking. [9] Noise-sensitive individuals have also been found to have more prominent symptoms of depression and anger [30] and individuals with high noise sensitivity have had more allergic complaints than persons with low sensitivity. [65] The Chemical Sensitivity Factor was associated with allergies and alcohol use among all subjects in this study.…”
Section: Weinstein's Noise Sensitivity Scale and Qeesi's Chemical Intmentioning
confidence: 98%
“…[2] Noise sensitivity has been either equally present in men and women [4][5][6] or in some studies women have scored higher on noise sensitivity. [7,8] It is a relatively stable trait [2,9] and has not been associated with auditory acuity. [2,[10][11][12] Noise sensitivity aggregates in families and the estimate of heritability is 36%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Although noise sensitivity is seldom the focus of public health research investigations, there is mounting evidence to suggest that noise sensitivity may be a health risk factor unto itself. [10][11][12][13][14] Noise sensitivity has been described as a complex and multifaceted construct that encompasses physiological reactions to noise, psychological reactivity and coping mechanisms. [15] Although noise sensitivity is often included as a potential moderator or covariate in acoustics-based and public health research on the effects of environmental noise, [8,16,17] there is limited evidence to suggest that noise sensitivity involves a sensory component.…”
Section: Introductionmentioning
confidence: 99%